The Role of Entrepreneurial Narratives in the Building and Sustaining of Successful Enterprises - Pande, Sangieta (Digital Repository of Theses, 2025)
In today's complex and competitive business landscape, entrepreneurial storytelling has evolved from a soft skill into a vital strategic tool. Entrepreneurs use their narratives to convey their vision, build trust with investors, engage employees, and foster emotional connections with customers. This dissertation examines the importance of entrepreneurial storytelling in establishing stakeholder trust, creating business legitimacy, and driving long-term growth, particularly within the Indian entrepreneurial context, where socio-cultural diversity adds another layer of narrative richness (Gartner, 2007; Lounsbury and Glynn, 2001). Based on a mixed-methods research design, this study combines qualitative findings from seven in-depth interviews with entrepreneurs across diverse industries—sustainable packaging, education, healthcare, and horticulture—with quantitative results from a systematic survey of 100 stakeholders. Thematic coding of the interviews produced seven primary findings: identity-based storytelling, authenticity of the story, storytelling technique development, adaptation to particular stakeholders, emotional and cultural congruence, internal sharing of stories, and quantitative measurement of narrative impact. The survey findings supported these outcomes: 73% of investors preferred scientifically sound and morally consistent stories, while 62% of customers were emotionally touched by narratives rich in emotion. Additionally, 55% of workers expressed an increased sense of belonging to the organisation when internal stories aligned with shared values. These trends signal that storytelling is not merely a brand program but a subtle, sophisticated communication method essential for building trust and engaging stakeholders. This study enhances the understanding of narrative identity theory by situating entrepreneurial storytelling within the framework of emerging markets and proposing a novel model of multi-stakeholder narrative alignment. It presents storytelling as a dynamic business capability that evolves concurrently with entrepreneurial identity and organizational maturity. Furthermore, the research underscores the critical role of storytelling in establishing legitimacy for enterprises operating in heavily regulated or impact-oriented industries (Jones and Li, 2017). Practical applications include suggestions for entrepreneurs to formalise storytelling as part of leadership and communication, teachers to integrate narrative modules into business education, investors to evaluate founders based on narrative coherence, and policymakers to promote ethical and inclusive storytelling at the grassroots level. Although the study's scope is specifically contextual to Indian businesses and self-reported data, it opens avenues for future research in digital storytelling, AI-curated stories, and longitudinal studies of narrative development (Polletta, 2006; Vaara and Tienari, 2011). Lastly, this dissertation establishes that authentic, stakeholder-centric storytelling is not secondary—it is a strategic leadership competency that drives connection, credibility, and long-term business success.